Pre-clinical year medical students' perception on the usage of Kahoot! quiz challenge as post-PBL assessment / Nurul Alimah Abdul Nasir, Siti Norashikin Mohd Tambeh and Omar Effat - Abdul Nasir, Nurul Alimah; Mohd Tambeh, Siti Norashikin; Effat, Omar (UiTM Press, 2020)
Formative assessment is an important tool to gauge the competence and performance of a medical student. This type of assessment enable the students to identify their strengths and weaknesses in order to improve their learning. The feedback given to students will motivate them to achieve their learning goals. The advancement of technology increases the usage of online-based assessment as it is more relevant and appealing especially to the younger generation. Online-based assessment such as Kahoot! offers immediate feedback and enhances the students' critical thinking and problem solving skills in a fun environment. These skills are important to be assessed especially following Problem-based Learning (PBL) sessions. PBL is adapted in many medical schools worlwide. Due to the nature of extensive learning objectives in PBL, it is important to have a practical formative assessment like quizzes in Kahoot! platform to assess the students' understanding. This study investigates the pre- clinical medical students' perception about Kahoot! quiz challenge as a formative assessment tool following PBL sessions.